Sustainability and Corporate Responsibility: A Comparison Between Greece and the UK - Olga Anastasia Stapountzi; James Robert Wallace (European Regional Science Association (ERSA), 2006)
Over the last five years companies are increasingly looking towards corporate responsibility (CR) as a means of satisfying stakeholder demands and improving company environmental and social performance. The terminology for corporate responsibility is interchangeable with sustainability and can vary depending upon the country or region the company operates. Non-financial reporting of companies helps to provide an indicator of which direction companies are taking, but does not always specify whether a company is benefitting the wider community outside of shareholders and employees. Although a great wealth of information is included in these reports, it is often difficult to compare them and in some cases not substantiated by assurance of the data or claims in the reports. Leading companies, in particular multinational companies, are decentralising CR/Sustainability functions to national levels to pursue different national or regional priorities. With little formal regulation from the EU on CR, the field is mainly self-regulated. Sustainable development is regulated more clearly with a particular focus on environmental management. The main purpose of this paper is to investigate different approaches to sustainability and corporate responsibility between Greek and UK companies. A particular focus will be on how companies operating in both countries manage environmental and social issues as a multinational. The priorities of these companies will also be examined to see if there are national or regional trends and if EU enlargement provides any opportunities or threats in the corporate view.
Keywords: 330